Couples Who Pray : The Most Intimate act Between a Man and a Woman - Rushnell, Squire D., 1938- and Duart, Louise (Nashvile Dallas Thomas Nelson, 2007)
In this entertaining, highly readable book, couples learn that a fabulous marriage can be the outcome of learning to pray together, a minimum of five minutes a day, causing a 20 to 30% increase in romance, conversation and happiness.
Include Appendix, Notes and Index
Keywords: Self-Actualization (Psychology) -- Self-Realization -- Creative Ability in Children